Non‐reassuring fetal status and anesthetic impact on cesarean section‐delivered very‐low‐birthweight infants. Issue 1 (5th October 2022) - Kim, Min Soo; Kim, HyoYun; Seo, Yumi; Yum, Sook Kyung
Abstract: Background: There is limited evidence concerning the impact on neonatal outcomes of different types of anesthesia used for cesarean delivery due to non‐reassuring fetal status (NRFS). We aimed to assess the impact of NRFS and general anesthesia (GA) on neonatal outcomes in very‐low‐birthweight (VLBW) infants delivered by cesarean section. Methods: Data were collected relating to VLBW infants admitted to our institution. Infants were grouped into no‐NRFS and NRFS groups and further subcategorized into GA and regional anesthesia (RA) subgroups. Neonatal outcomes were evaluated based on the presence of NRFS and the type of anesthesia. Results: A total of 356 infants were included. The GA subgroup in the no‐NRFS group had higher requirements for respiratory support. However, GA was not associated with adverse neonatal outcomes based on the multivariable logistic regression analysis except for 5 min Apgar score <5. On the other hand, NRFS was associated with an increased risk of 5 min Apgar score <5 [adjusted odds ratio (aOR) 2.062, 95% confidence interval (CI) 1.064–3.997], use of high‐frequency ventilation (aOR: 2.891, 95% CI: 1.477–5.658), and pulmonary hypertension (aOR: 2.890, 95% CI: 1.436–5.819). Conclusions: In our cohort of VLBW infants, NRFS was a significant risk factor for a low 5 min Apgar score, increased respiratory support requirement, and pulmonary hypertension. Accurate assessment of fetal well‐being, timely delivery, and presence of a resuscitation team fully aware of perinatal conditions and anesthetic impact is important.